PDBCharges: Quantum-Mechanical Partial Atomic Charges for PDB Structures - Schindler, Ondřej; Svoboda, Tomáš; Rošinec, Adrián; Raček, Tomáš; Bučeková, Gabriela; Tichý, Dominik; Berka, Karel; Svobodová, Radka (Nucleic acids research, 2025)
The Protein Data Bank (PDB) is the largest database of experimentally determined protein structures, containing more than 230 000 experimentally determined structures. The chemical reactivity of proteins is based on the electron density distribution, which is usually approximated by partial atomic charges. However, because of the size and high variability, there is not yet a universal and accurate tool for calculating the partial atomic charges of these structures. For this reason, we introduce the web application PDBCharges: a tool for quick calculation of partial atomic charges for protein structures from PDB. The charges are calculated using the recent semi-empirical quantum-mechanical method GFN1-xTB, which reproduces PBE0/TZVP/CM5 charges. The computed partial atomic charges can be downloaded in common data formats or visualized online via the powerful Mol* Viewer. The PDBCharges application is freely available at https://pdbcharges.biodata.ceitec.cz and has no login requirement.
Keywords: Static Electricity; internet; statická elektřina; Protein Conformation; Internet; software; databáze proteinů; Quantum Theory; Software; Databases, Protein; Proteins; proteiny; konformace proteinů; kvantová teorie